Experimental Study on the Influence of Preheated Air and Air-fuel Ratio on the Combustion Temperature of Natural Gas Cupola. (November 2020) - Li, Guangpeng; Zhou, Hengchao; Wang, Qi
Abstract: In order to improve the combustion temperature, this paper took 2t/h natural gas cupola as an example, designed the performance experimental systems, discussed and analyzed the influence of critical factors such as air-fuel ratio and preheated air temperature on the combustion temperature in the furnace. The results showed that the combustion temperature can reach the highest value by controlling the air-fuel ratio around 9. 8. The increase or decrease of air-fuel ratio can reduce the temperature, increasing the amount of air decreased the amount of smoke and taking away a lot of the heat, and decreasing the amount of air resulted in incomplete combustion. The combustion temperature can be increased by increasing the temperature of preheated air. The temperature rise rate is about 35°C for every 100°C increase below 200°C, and 55°C for every 100°C increase after 200°C.